REPRESENTASI EKSISTENSI PEREMPUAN DALAM NOVEL TERUSIR KARYA HAMKA (KAJIAN SASTRA FEMINIS) - Fadiyah, Syifa; Nawawi, Nawawi (Jurnal Bahastra, 2023)
This study aims to describe the forms of women's existence representation in the novel "Terusir" by Hamka. The research data was collected using a qualitative descriptive method with a literary feminism approach. Data collection techniques included library research, reading, and note-taking. The data analysis employed a descriptive approach, involving data classification, data reduction, data presentation, and conclusion. The findings of this study reveal the forms of women's existence representation in three aspects. Firstly, the character of the woman who displays Mariah's character as a woman who is honest, has a strong personality, is independent, never gives up, is patient, weak, afraid, kind, and resigns. Secondly, women's existence is manifested as a strategy of resistance, including their ability to work, become intellectuals, bring about social transformations, and refuse to be someone else. Thirdly, trigger factors for existence that are influenced by gender differences, giving rise to forms of gender injustice experienced by Mariah such as marginalization, subordination, stereotypes, violence, and workload.